Determination of Cr, Se, Ge, and V in Hypothyroidism Patients by Using Graphite Furnace Atomic Absorption Spectrometry and mixture matrix modification - Halah Hamid Hammadi (College of Pharmacy / Mustansiriyah University, 2023)
A simple, accurate and rapid method was developed for routine determination of trace elements in blood serum. The method based on the direct determination for Cr, Se, Ge, and V in hypothyroidism patients before therapy. By using atomic absorption spectrometry with graphite surface coated and uncoated pyrolysis GF-AAS, and a mixture of palladium nitrate and magnesium nitrate as the matrix modifier, with deuterium background correction and no sample pretreatment except dilution was necessary. This permitted direct determination hence the risk of sample contamination was reduced. Further, the use of graphite surface-coated GF-AAS decreased the ashing and atomization temperatures of Cr, Ge, and V to values that were lesser than the corresponding values obtained using uncoated pyrolysis GF-AAS, by 100°C; in case of Se, the atomization temperature decreased to a value that was 200°C lesser than that obtained using uncoated pyrolysis GF-AAS. A mixture of (3µL) palladium nitrate, and (2µL) magnesium nitrate was successfully applied to improve the sensitivity, reproducibility, recovery, limit of detection and the accuracy of the measurements. The correlation coefficients of the calibration curves of Cr, Se, Ge, and V were found to be (0.9999, 0.9999, 0.9995 and 0.9999) respectively, the relative standard deviation of the measurements for Cr, Se, Ge and V were (0.027, 0.075, 0.054 and 0.068) respectively. The statistical analysis of the acquired data showed acceptable accuracy. The analyses thus performed indicated that the levels of serum trace elements Cr, Se, Ge, and V in hypothyroidism patients were lower than those in the control group.